Transfusion-dependence Anemia in a Middle-Age Woman under longlasting therapy with Eslicarbazepine and Quetiapine: A Case Report and Drug-related Erythroid Toxicity review - Herreros, Paula Gili; Fernández, Juan José Gil-; Iglesias, Francisco José de Abajo; García-Suárez, Julio (Archives of Clinical and Medical Case Reports, 2026)
Antiepileptic and antipsychotic drugs are related with the development of different hematological toxicities both in short and long-term therapies. We present a case report of a patient with secondary structural focal epilepsy and behavioral disorder under prolonged therapy with eslicarbazepine and quetiapine who developed a 3-year long-lasting severe and recurrent hyporegenerative transfusion-dependent anemia. Recombinant-human erythropoietin and corticosteroids were successfully used in each relapse of severe anemia. Eslicarbazepine was first gradually replaced by lacosamide with hematological improvement and after a new relapse quetiapine was also replaced by paliperidone. After complete discontinuation of both eslicarbazepine and quetiapine a 1-year lasting therapy-free sustained hematologic recovery has been achieved without further relapses. This is the first case in the literature to directly associate eslicarbazepine, as previously carbamazepine, with erythroid toxicity and also points to quetiapine for central hematological toxicity. Our clinical observation underscores the importance of considering drugs as a possible cause of anemia in patients under prolonged antiepileptic and antipsychotic therapies especially in combination regimens.